For this case we must solve each of the functions.
We have then:
f (x) = x2 - 9, and g (x) = x - 3
h (x) = (x2 - 9) / (x - 3)
h (x) = ((x-3) (x + 3)) / (x - 3)
h (x) = x + 3
f (x) = x2 - 4x + 3, and g (x) = x - 3
h (x) = (x2 - 4x + 3) / (x - 3)
h (x) = ((x-3) (x-1)) / (x - 3)
h (x) = x-1
f (x) = x2 + 4x - 5, and g (x) = x - 1
h (x) = (x2 + 4x - 5) / (x - 1)
h (x) = ((x + 5) (x-1)) / (x - 1)
h (x) = x + 5
f (x) = x2 - 16, and g (x) = x - 4
h (x) = (x2 - 16) / (x - 4)
h (x) = ((x-4) (x + 4)) / (x - 4)
h (x) = x + 4
Answer:
answer is A. cosine
Step-by-step explanation:
Answer:
Option 5 & 6
Step by Step Explanation:
8 / 0.95 = 8.4 ( wrong )
18 / 2.2 = 8.18 ( wrong )
47.6 / 3.9 = 16.41 ( wrong )
10.6 / 1.89 = 5.6 ( wrong )
71.9 / 6.5 = 11.061 ( correct )
123.4 / 9.2 = 13.41 ( correct )
157.4 / 16.4 = 9.59 ( wrong )
hope this helps! please give brainliest and thanks!!!